SOSIALISASI DIGITAL MARKETING DAN EDUKASI PERPAJAKAN DI PADUKUHAN SUREN WETAN - Adia Adi Prabowo; E. Budi Setiawan; Ida Bagus Nyoman Udayana (LPPM ITB AAS Indonesia Surakarta, 2023)
This community service aims to provide understanding to UMKM in Suren Wetan hamlet about Taxation and digital marketing. It is hoped that with this activity, UMKM in this area,understand and know how to calculate personal and business taxes and understand how to do marketing using digital marketing. The problems that exist in the community, especially UMKM in Suren Wetan hamlet, are the lack of understanding of digital marketing in promoting their products and marketing their products, mostly using traditional or conventional method and lack of understanding of UMKM regarding taxation, Based on these problems, digital marketing training and knowledge related to taxation are needed. This training ultimately helps UMKM understand digital marketing and how to use it. Overall, the training went well, and management was supported to ensure that the training was successfully implemented without significant obstacles. The output produced in this community service will be in the form of HaKi.